Fiscal externalities in local tax competition: empirical evidence from a panel of German jurisdictions - Thiess Buettner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper is concerned with fiscal externalities arising from local taxation of a mobile factor. Using a panel of more 1100 local jurisdictions it provides empirical evidence on how the local tax rate as well as the tax rate in the neighborhood affect the local tax base. The results support the existence of fiscal externalities: an increase in the tax rate of local neighbors exerts a positive effect on the tax base whereas an increase of the own tax rate has a negative effect, and a joint increase of the tax rate at the local jurisdiction and in its neighborhood has no significant effect on the interjurisdictional distribution of the tax base. However, in the considered case tax competition is alleviated by revenue sharing rules which reduce the jurisdictions' incentive to lower tax rates in order to attract capital.
Keywords: H73; H72; D62; C23; H71; 330; Local Capital Taxation; Fiscal Externalities; Tax Competition; Fiscal Equalization Grant; Empirical Investigation; Panel Data; Gemeindesteuer; Steuerwettbewerb; Kommunaler Finanzausgleich; Externer Effekt; Schätzung; Deutschland